Abstract ID: 122 Verification of dose estimation for Monte-Carlo based treatment planning system for boron neutron capture therapy. (October 2017) - Kumada, Hiroaki; Takada, Kenta; Aihara, Teruhito; Matsumura, Akira; Sakurai, Hideyuki; Sakae, Takeji
Abstract : University of Tsukuba is developing a treatment device for accelerator-based for boron neutron capture therapy (BNCT). In the project, not only the treatment device (neutron source) but also several peripheral devices requiring in BNCT treatment[1] . As part of the development, a Monte-Carlo based treatment planning system (Developing code: Tsukuba-Plan) applicable to BNCT is also being developed. Regarding Monte-Carlo dose calculation engine, the Tsukuba-Plan has employed PHITS as the multi-purpose Monte Carlo Particle and Heavy Ion Transport code System. PHITS allows to calculate behaviors for several radiations such as neutrons, photons, protons and heavy-ions[2] . Therefore the Tsukuba-Plan with PHITS enables to perform dose estimation for not only BNCT but also particle radiotherapy and X-ray therapy. A prototype of the Tsukuba plan has been completed. At present, we are carrying out several verifications for the Tsukuba-Plan. To verify dose estimation accuracy of the system, some experiments with a water phantom were simulated by using the Tsukuba-Plan, and the calculation results were compared with experimental data. In the experiments, gold foils and TLDs were set in the phantom, and then the phantom was set to in front of the beam aperture of the neutron source for BNCT device. Neutron beam was irradiated to the phantom, finally two-dimensional distributions for thermal neutron flux and gamma-ray dose in the phantom were measured. On the other hand, regarding simulation of the experiments with the Tsukuba-Plan, CT images of the water phantom were loaded to Tsukuba-Plan, and the irradiation conditions were represented. And calculations of two-dimensional distributions for both of thermal neutron flux and gamma-ray dose in the phantom were determined by using PHITS. The calculation results obtained from the Tsukuba-Plan were compared with the experimental values. The calculation values were in good agreement with the experimental values within statistical errors and experimental errors. The verification results demonstrated that Tsukuba-Plan enables to perform dose estimation for BNCT. Clinical group of University of Tsukuba plans to perform clinical trial for BNCT by using the neutron source for BNCT treatment device in the near future. Tsukuba-Plan will be applied to the clinical trials in practical use.